Utilization of Artificial Intelligence (AI) to Enhance Historical Literacy and Learning Interest of Grade 10 Students at Senior High School - Firdayanti Pidda; Idrus A. Rore; Fajar Nugroho (Universitas Islam Negeri Palopo, 2026)
This study investigates the utilization of Artificial Intelligence (AI) to enhance historical literacy and learning interest among Grade 10 students at SMA Negeri 7 Palu. Low student engagement in history learning remains a persistent challenge due to teacher-centered instruction, rote memorization, and limited contextual learning experiences. This research employed a qualitative descriptive approach involving one history teacher and 35 Grade 10 students. Data were collected through classroom observation, interviews, and documentation. The study found that AI platforms such as ChatGPT, Gemini, and Perplexity AI increased students’ participation, confidence, curiosity, and motivation in history learning because AI provides interactive, personalized, and accessible learning experiences. Students became more active in classroom discussions and more confident in expressing historical opinions after independently exploring historical information through AI-assisted learning. The findings also indicate that teachers continue to play a crucial role as facilitators who guide students in critically evaluating AI-generated information and ensuring ethical technology use. The study concludes that pedagogically guided AI integration contributes positively to student-centered history learning and promotes stronger learning interest and historical literacy.